2012
DOI: 10.1182/blood-2011-07-369934
|View full text |Cite
|
Sign up to set email alerts
|

DNMT3A mutations in acute myeloid leukemia: stability during disease evolution and clinical implications

Abstract: DNMT3A mutations are associated with poor prognosis in acute myeloid leukemia (AML), but the stability of this mutation during the clinical course remains unclear. In the present study of 500 patients with de novo AML, DNMT3A mutations were identified in 14% of total patients and in 22.9% of AML patients with normal karyotype. DNMT3A mutations were positively associated with older age, higher WBC and platelet counts, intermediate-risk and normal cytogenetics, FLT3 internal tandem duplication, and NPM1, PTPN11,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
201
5
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 215 publications
(224 citation statements)
references
References 25 publications
16
201
5
2
Order By: Relevance
“…We and others 24,25,29 --31,44 found that DNMT3A mutations were strongly associated with FAB M4/M5 subtypes, and often co-occurred with NPM1 or IDH1 mutations in AML patients, suggesting that the oncogenic actions of these mutations are not redundant. DNMT3A mutations were reported to be associated with older age, 24,25,30,31 but this feature was not observed in our cohort of adult CN-AML. Nevertheless, a link between age and the incidence of DNMT3A mutations is likely as these mutations seem to be extremely rare (o1%) in pediatric AML.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…We and others 24,25,29 --31,44 found that DNMT3A mutations were strongly associated with FAB M4/M5 subtypes, and often co-occurred with NPM1 or IDH1 mutations in AML patients, suggesting that the oncogenic actions of these mutations are not redundant. DNMT3A mutations were reported to be associated with older age, 24,25,30,31 but this feature was not observed in our cohort of adult CN-AML. Nevertheless, a link between age and the incidence of DNMT3A mutations is likely as these mutations seem to be extremely rare (o1%) in pediatric AML.…”
Section: Discussioncontrasting
confidence: 77%
“…Factors related to patient and disease characteristics, and differences in treatment modalities may account for these different findings, but the exact reasons for this discordance remain unknown. DNMT3A mutations rarely occur in patients with CEBPA mutations, 30 especially in those with double CEBPA mutations, 51 and the clinical outcome of AML patients who carry both mutations is yet uncertain. 51 In our cohort, the prognostic impact of DNMT3A mutations in patients with CEBPA mutations was not evaluable, as CEBPA and DNMT3A mutations were mutually exclusive.…”
Section: Discussionmentioning
confidence: 99%
“…89 Although previous studies clearly pointed to an oncogenic role of DNMT3A in cancer, the recent discovery of genetic mutations of DNMT3A in acute myeloid leukemia (AML) suggested that its role in cancers may be more complex than was previously believed. [11][12][13][14][15][16][17][18][19][20][21][22][23] These highly recurrent DNMT3A mutations were closely associated with poor outcome in patients with AML. However, the functional implications of these mutations are still poorly understood.…”
Section: The Dual Roles Of Dnmt3a In Cancermentioning
confidence: 99%
“…10 However, several inactivating mutations of DNMT3A in myeloid malignancies [11][12][13][14][15][16][17][18][19][20][21][22][23] and loss of DNMT3A activity at advanced tumor stages 24 were recently identified. In addition, novel roles of DNMT3A in the hematopoiesis system 25 and in the age-related decline of cognition 26 have been revealed.…”
Section: Introductionmentioning
confidence: 99%
“…180,181 Similarly, the DMNT3A mutation is found at a higher percentage in adult (15%-20%) compared to childhood (2%) AML. 63,182,183 The FLT3-ITD mutation is found in 25% of adult and 15% of childhood AML. 43,184 Two less well-studied mutations that may serve as MRD markers include CEBPA and MLLpartial tandem duplications.…”
Section: Rq-pcrmentioning
confidence: 99%